Psychological functioning, coping styles and their relationship to appraisal of physical limitations following invasive surgical procedures for soft-tissue sarcoma: A qualitative study - Košir, U; Denis-Larocque, G; Tsimicalis, A; Freeman, C; Turcotte, RE; Cury, F; Alcindor, T; Goulding, K (Wiley, 2020)
Background and Objectives This study explored psychological functioning and coping styles in adult patients with soft‐tissue sarcoma who underwent surgical procedures in a single expert sarcoma medical center in Canada.